Interactive effects between plant functional types and soil factors on tundra species diversity and community composition. Issue 22 (17th October 2016) - Iturrate‐Garcia, Maitane; O'Brien, Michael J.; Khitun, Olga; Abiven, Samuel; Niklaus, Pascal A.; Schaepman‐Strub, Gabriela
Abstract: Plant communities are coupled with abiotic factors, as species diversity and community composition both respond to and influence climate and soil characteristics. Interactions between vegetation and abiotic factors depend on plant functional types (PFT) as different growth forms will have differential responses to and effects on site characteristics. However, despite the importance of different PFT for community assembly and ecosystem functioning, research has mainly focused on vascular plants. Here, we established a set of observational plots in two contrasting habitats in northeastern Siberia in order to assess the relationship between species diversity and community composition with soil variables, as well as the relationship between vegetation cover and species diversity for two PFT (nonvascular and vascular). We found that nonvascular species diversity decreased with soil acidity and moisture and, to a lesser extent, with soil temperature and active layer thickness. In contrast, no such correlation was found for vascular species diversity. Differences in community composition were found mainly along soil acidity and moisture gradients. However, the proportion of variation in composition explained by the measured soil variables was much lower for nonvascular than for vascular species when considering the PFT separately. We also found different relationships between vegetation cover and species diversity according the PFT and habitat. In support of niche differentiation theory, species diversity and community composition were related to edaphic factors. The distinct relationships found for nonvascular and vascular species suggest the importance of considering multiple PFT when assessing species diversity and composition and their interaction with edaphic factors. Synthesis : Identifying vegetation responses to edaphic factors is a first step toward a better understanding of vegetation–soil feedbacks under climate change. Our results suggest that incorporating differential responses of PFT is important for predicting vegetation shifts, primary productivity, and in turn, ecosystem functioning in a changing climate. Abstract : Despite the differential processes interacting with plant functional types (PFT) to promote community assembly and ecosystem functioning, research is strongly biased toward vascular plants. Here, we show that the relationships of species diversity and community composition with edaphic factors are PFT‐specific in the Siberian Arctic tundra. Our results suggest that incorporating nonvascular vegetation and differential responses of PFT in dynamic vegetation models is crucial for projecting vegetation shifts, primary productivity, and in turn, ecosystem functioning in a changing climate.